Distinct neuronal populations in the basal forebrain encode motivational salience and movement - Avila, Irene; Lin, Shih-Chieh (Frontiers in Behavioral Neuroscience, 2014)
Basal forebrain (BF) is one of the largest cortically-projecting neuromodulatory systems in the mammalian brain, and plays a key role in attention, arousal, learning and memory. The cortically projecting BF neurons, comprised of mainly magnocellular cholinergic and GABAergic neurons, are widely distributed across several brain regions that spatially overlap with the ventral striatopallidal system at the ventral pallidum (VP). As a first step toward untangling the respective functions of spatially overlapping BF and VP systems, the goal of this study was to comprehensively characterize the behavioral correlates and physiological properties of heterogeneous neuronal populations in the BF region. We found that, while rats performed a reward-biased simple reaction time task, distinct neuronal populations encode either motivational salience or movement information. The motivational salience of attended stimuli is encoded by phasic bursting activity of a large population of slow-firing neurons that have large, broad, and complex action potential waveforms. In contrast, two other separate groups of neurons encode movement-related information, and respectively increase and decrease firing rates while rats maintained fixation. These two groups of neurons mostly have higher firing rates and small, narrow action potential waveforms. These results support the conclusion that multiple neurophysiologically distinct neuronal populations in the BF region operate independently of each other as parallel functional circuits. These observations also caution against interpreting neuronal activity in this region as a homogeneous population reflecting the function of either BF or VP alone. We suggest that salience- and movement-related neuronal populations likely correspond to BF corticopetal neurons and VP neurons, respectively.